Cultural Diversity and its Role in the Sociocultural Development of Humankind - Zaitsev, Mykola; Shevchuk, Dmytro; Khudoba, Kateryna (Journal of Education Culture and Society, 2025)
Aim. The article aims to analyse the problem of cultural diversity in the situation of intensifying globalisation processes. The authors emphasise that cultural diversity is constituted in our time as one of the essential problems of cultural studies and humanities. They aim to show that the existing cultural diversity is the result of the adaptation and development of various natural and sociocultural circumstances in which people lived in previous eras. Methods. The method of the current investigation is the interpretive analysis of modern cultural phenomena. Results. It is emphasised that the interaction of cultures plays a significant role in the formation of the cultural diversity of humankind. The authors note that the change in human attitudes to the natural environment and changes in sociocultural circumstances due to globalisation processes create, at first glance, the erosion of cultural diversity and contribute to the formation of unified forms of collective life and individual existence in the world. Conclusion. The authors conclude that the contradictions of globalisation processes are forming new forms and ways of cultural diversity. Cultural diversity is constituted in our time as one of the fundamental problems of socio-humanitarian knowledge because it will preserve or become a thing of the past and depend on the anthropological horizons of the sociocultural progress of humankind. The existing cultural diversity results from adapting and developing various natural and sociocultural circumstances in which people lived in previous epochs.